Bis(2-aminopyrimidine-[kappa]N1)aqua(nitrato-[kappa]O)(nitrato-[kappa]2O,O')zinc(II) - Gao, S.; Ng, S.W. (International Union of Crystallography, 2010)
The water-coordinated Zn atom in the title monoaqua zinc nitrate adduct of 2-aminopyrimidine, [Zn(NO3)(2)(C4H5N3)(2)-(H2O)], is bonded to a monodentate nitrate ion and is chelated by the other nitrate ion. The heterocyclic ligands coordinate through ring N-donor sites. The coordination geometry about the Zn(II) atom is a distorted octahedron. Intramolecular N-H center dot center dot center dot O hydrogen bonds occur. In the crystal, adjacent adduct molecules are linked by O- H center dot center dot center dot O, O-H center dot center dot center dot N and N-H center dot center dot center dot O hydrogen bonds into a layer motif parallel to ( 001).